Dual phenotypes in recurrent astrocytoma, IDH-mutant; coexistence of IDH-mutant and IDH-wildtype components: a case report with genetic and epigenetic analysis - Junya Yamaguchi; Fumiharu Ohka; Masafumi Seki; Kazuya Motomura; Shoichi Deguchi; Yoshiki Shiba; Yuka Okumura; Yuji Kibe; Hiroki Shimizu; Sachi Maeda; Yuhei Takido; Ryo Yamamoto; et al. (Acta Neuropathologica Communications, 2024)
Abstract Mutations in the isocitrate dehydrogenase (IDH) gene are recognized as the key drivers in the oncogenesis of astrocytoma and oligodendroglioma. However, the significance of IDH mutation in tumor maintenance and malignant transformation has not been elucidated. We encountered a unique case of IDH-mutant astrocytoma that, upon malignant transformation, presented two distinct intratumoral components: one IDH-wildtype and one IDH-mutant. The IDH-wild-type component exhibited histological findings similar to those of small cell-type glioblastoma with a higher Ki-67 index than the IDH-mutant component. Despite their genetic divergence, both components exhibited similar comprehensive methylation profiles within the CpG island and were classified into methylation class of “Astrocytoma, IDH-mutant; High Grade” by the German Cancer Center (DKFZ) classifier v11.4. Phylogenetic analysis demonstrated that the IDH-wildtype component emerged as a subclonal component of the primary tumor. Detailed molecular analyses revealed that the loss of the IDH mutation was induced by the hemizygous loss of the entire arm of chromosome 2, on which IDH1 gene is located. Notably, the IDH-wild-type subclones uniquely acquired CDKN2A/B homozygous deletion and PDGFRA amplification, which is a marker of the aggressive phenotype of astrocytoma, IDH-mutant. Because these genetic abnormalities can drive oncogenic pathways, such as the PI3K/AKT/mTOR and RB signaling pathway, IDH-mutant gliomas that acquired these mutations were no longer dependent on the initial driver mutation, the IDH mutation. Molecular analysis of this unique case provides insight that in a subset of astrocytoma, IDH-mutant that acquired these genetic abnormalities, IDH mutation may not play a pivotal role in tumor growth and acquisition of these genetic abnormalities may contribute to the acquisition of resistance to IDH inhibitors.